2021
DOI: 10.3389/fpls.2021.781236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light on Secondary Metabolite Biosynthesis in Medicinal Plants

Abstract: Secondary metabolites (SMs) found in medicinal plants are one of main sources of drugs, cosmetics, and health products. With the increase in demand for these bioactive compounds, improving the content and yield of SMs in medicinal plants has become increasingly important. The content and distribution of SMs in medicinal plants are closely related to environmental factors, especially light. In recent years, artificial light sources have been used in controlled environments for the production and conservation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 141 publications
2
36
0
Order By: Relevance
“…Plants respond to light via photoreceptors and employ multiple transcription factors to regulate anthocyanin metabolites formation (Zhang et al, 2021). To further identify the key regulation factors, we used WGCNA method to comprehensively analyze metabolites and key genes in perilla.…”
Section: Discussionmentioning
confidence: 99%
“…Plants respond to light via photoreceptors and employ multiple transcription factors to regulate anthocyanin metabolites formation (Zhang et al, 2021). To further identify the key regulation factors, we used WGCNA method to comprehensively analyze metabolites and key genes in perilla.…”
Section: Discussionmentioning
confidence: 99%
“…Plant cellular processes and primary/secondary metabolism are disrupted under unfavorable light conditions [ 4 , 35 , 36 ]. Excessive light triggers ROS generation and photooxidative stress primarily leads to lipid peroxidation and β-carotene oxidation, which further produces reactive carbonyl species (RCS) and causes H 2 O 2 accumulation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shade treatment with sunshade nets influenced the triterpene saponin accumulation and its related gene expression in Aralia elata [ 27 ]. Shade also induces changes in light quality, such as far-red light (710–850 nm), affecting flavonoid biosynthesis via phytochrome-mediated responses [ 19 , 20 , 40 ]. A recent, interesting work showed that drought prior to death may open a ‘metabolic black box’, targeting particular secondary metabolic pathways, weakening defenses against natural enemies, and contributing to the risk of drought-induced mortality in P. sylvestris [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathways of carbon-based phenylpropanoids and terpenoids are crucial for producing defense-related metabolites under stress conditions [ 15 , 16 , 17 ]. Mostly reported by horticultural crop studies, flavonoids are the most important polyphenols produced from the pathway of phenylpropanoid biosynthesis, and the accumulation of flavonoids is mostly affected by light intensity [ 18 ] or light quality [ 19 , 20 ]. In a grape orchard, a lower light intensity within the canopy decreased the supply of carbon precursors to the pathways of phenylpropanoid and flavonoid biosynthesis, resulting in lower levels of phenolic compounds, such as flavonols, flavan-3-ols, and procyanidins, in the exocarps of grapes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%